2018
DOI: 10.5194/amt-11-5901-2018
|View full text |Cite
|
Sign up to set email alerts
|

The MIPAS/Envisat climatology (2002–2012) of polar stratospheric cloud volume density profiles

Abstract: Abstract. A global data set of vertical profiles of polar stratospheric cloud (PSC) volume density has been derived from Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) space-borne infrared limb measurements between 2002 and 2012. To develop a well characterized and efficient retrieval scheme, systematic tests based on limb-radiance simulations for PSCs from in situ balloon observations have been performed. The finally selected wavenumber range was 831–832.5 cm−1. Optical constants of nitric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Most recently, Höpfner et al. (2018) found that for coincident PSC scenes classified as predominantly (>50%) STS by CALIOP, there was good agreement between the magnitudes and vertical profile shapes of CALIOP and MIPAS particle VD. Here, we extend the results of Höpfner et al.…”
Section: Psc Spatial and Temporal Distributions And Compositionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most recently, Höpfner et al. (2018) found that for coincident PSC scenes classified as predominantly (>50%) STS by CALIOP, there was good agreement between the magnitudes and vertical profile shapes of CALIOP and MIPAS particle VD. Here, we extend the results of Höpfner et al.…”
Section: Psc Spatial and Temporal Distributions And Compositionmentioning
confidence: 95%
“…Generally favorable comparisons between MIPAS and earlier (Version 1) CALIOP PSC composition results were found by Höpfner et al (2009) using the 2-CR method (Section 2.1.1.2) and more recently by Spang et al (2016) using a new Bayesian classifier approach. Most recently, Höpfner et al (2018) found that for coincident PSC scenes classified as predominantly (>50%) STS by CALIOP, there was good agreement between the magnitudes and vertical profile shapes of CALIOP and MIPAS particle VD. Here, we extend the results of Höpfner et al (2009) by comparing the CALIOP v2 and MIPAS Bayesian PSC composition classifications for the 2006-2011 overlap period using more stringent coincidence criteria (<1 h in time and <100 km in radial distance from the MIPAS tangent point) and further restricting the comparison to homogeneous CALIOP scenes, defined by the criteria that more than 50% of the CALIOP individual 5-km measurement samples within the MIPAS FOV are PSCs and more than 75% of those samples are classified as a single CALIOP composition.…”
Section: Caliop Versus Mipasmentioning
confidence: 96%
See 1 more Smart Citation
“…Both effects can be observed at the MIPAS spectral resolution (Spang et al, 2004;Greenhough et al, 2005;Höpfner et al, 2006). Spectral signatures of polar stratospheric clouds can also be observed in MIPAS spectra (Höpfner et al, 2018). This means that, while on one hand cloud information can be extracted from MIPAS measurements, on the other hand cloud radiative effects can mask the spectral features of the target gases, strongly affecting their retrieval.…”
Section: Improved Cloud-filteringmentioning
confidence: 98%
“…Various climatologies of PSCs based on satellite measurements were published in the last years (Spang et al, 2018;Höpfner et al, 2018;Pitts et al, 2018). The application of machine learning for the detection of PSCs from satellite measurements has been discussed recently (Sedona et al, 2020).…”
Section: Introductionmentioning
confidence: 99%